Reproductive rights and options available to women infected with HIV in Ghana: perspectives of service providers from three Ghanaian health facilities. - Laar, A.K. (My University, 2013)
Background: Owing to improved management of HIV and its associated opportunistic infections, many HIV-positive persons of reproductive age are choosing to exercise their right of parenthood. This study explored the knowledge of health workers from two Ghanaian districts on the reproductive rights and options available to HIV-positive women who wish to conceive.Methods: Facility-based cross-sectional in design, the study involved the entire population of nurse counselors (32) and medical officers (3) who provide counseling and testing services to clients infected with HIV. Both structured and in-depth interviews were conducted after informed consent.Results: Two main perspectives were revealed. There was an overwhelmingly high level of approbation by the providers on HIV-positive women's right to reproduction (94.3%). At the same time, the providers demonstrated a lack of knowledge regarding the various reproductive options available to women infected with HIV. Site of facility, and being younger were associated with practices that violated client's right to contraceptive counseling (p < 0.05) in each case. Some of the providers openly expressed their inability to give qualified guidance to HIV-positive women on the various reproductive options.Conclusions: Taken together, these findings suggest that many HIV-positive clients do not receive comprehensive information about their reproductive options. These findings highlight some of the problems that service providers face as HIV counselors. Both service providers and policy makers need to recognize these realities and incorporate reproductive health issues of HIV-persons into the existing guidelines. © 2013 Laar; licensee BioMed Central Ltd.